Real‐world prevalence and burden of genital eczema in atopic dermatitis: A multicenter questionnaire‐based study. Issue 5 (5th March 2021) - Woo, Yu Ri; Han, Yujin; Lee, Ji Hae; Lee, Young Bok; Kim, Jung Eun; Kim, Miri; Park, Chul Jong; Lee, Ji Hyun; Cho, Sang Hyun
Abstract: The involvement of genital lesions in patients with atopic dermatitis (AD) is poorly understood. Moreover, clinical characteristics, potentially related factors, and impact on the quality of life (QOL) of genital eczema in patients with AD are also largely unknown. This study aims to evaluate the prevalence and burden of genital eczema in patients with AD. A prospective cross‐sectional study recruited a total of 220 patients diagnosed with AD. The participants were asked to complete the self‐administrated questionnaire asking sociodemographic characteristics, details about their AD, and individual experiences of their genital eczema. Among 220 responders, 99 patients (45.00%) reported that they had experienced genital eczema at some time during the course of AD. Longer disease duration (odds ratio [OR], 2.29; 95% confidence interval [CI], 1.13–4.62; p = 0.02), marital status (OR, 0.43; 95% CI, 0.21–0.89; p = 0.003), involvement of the trunk (OR, 3.44; 95% CI, 1.81–6.52; p = 0.001), and involvement of the nipple (OR, 6.20; 95% CI, 1.39–27.63; p = 0.017) were the significant associated factors for the presence of genital eczema among patients with AD. Of note, the severe impairment of genital eczema‐specific QOL was observed in 28.29% of AD patients with genital eczema. Especially, female sex (OR, 2.22; 95% CI, 0.84–5.82; p = 0.04) was more associated with severe impairment of genital eczema‐specific QOL. Many patients with AD suffer from the genital presentation of the disease. Moreover, genital involvement of the disease has a significant impact on the QOL of patients with AD. We suggest that more attention should be paid to the genital presentation of the disease to increase QOL and provide further delicate treatment of patients with AD.